Enabling and Constraining Conditions of Professional Teacher Agency: The South African Context. (January 2017) - Long, Caroline; Graven, Mellony; Sayed, Yusuf; Lampen, Erna
The South African people have a history of resistance to domination, injustice and inequality. It is therefore surprising that there has been an increase in social inequality, since the start of political democracy in 1994. Recently, the five teachers' unions refused to administer the Annual National Assessments. This action indicates some resistance to domination. In this article, we will first explore the concept of professional teacher agency in the light of teaching, both as a profession and as a vocation constrained by prior experience and social context. Second, we will draw on the current assessment context to outline its problems and perspectives, and consider within this context the enabling and constraining conditions for teacher agency. Third, we will discuss how assessment as a tool for monitoring teacher performance may impede the conditions for quality education. Finally, we would like to propose that the delivery of a good quality education requires adopting a teacher education model which supports agency, and in which the design of diagnostic assessments is locally responsive.